La Gamificación en el proceso de aprendizaje - García Miniguano, Jimmy Alexander (2023)
The objective of this research work is to determine the influence of gamification on the learning process in the students of the Educational Unit "Gral. Leonidas Plaza Gutiérrez, 2022”. From the methodological point of view, this study is based on the quantitative approach because the variables related to gamification and the learning process will be measured, its level will be descriptive, explanatory, with a non-experimental and cross-sectional study design. The sample made up of 80 students from the population under study, to whom questionnaires with validity and reliability were applied to measure the variables studied. The applied method was of the deductive type, through which it was possible to infer and understand the problem to develop strategies in the classroom, which allow the development of the learning process.